2004
DOI: 10.1055/s-2004-829043
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Breast Conservation Deformity

Abstract: The era of breast conserving treatment of early-stage breast carcinoma has created reconstructive challenges for the plastic surgeon. Although good to excellent cosmetic outcomes occur in the majority of patients, a significant number could benefit from additional reconstructive measures. Because of the need for continuing surveillance following breast-conserving therapy, estimated at 5-10% after fifteen years, plastic surgeons should choose techniques that do not interfere with the detection of recurrent brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 45 publications
1
19
0
3
Order By: Relevance
“…In addition, reconstructive techniques that involve relocation of glandular tissue make reexcision difficult in cases where close or positive margins are observed in the permanent abnormality. 4 Although the lateral thoracodorsal fasciocutaneous flap technique did not obscure the original lumpectomy space, careful and coordinated planning with the oncologic surgeon is important in the event that reexploration is necessary. Similar to reduction mammaplasty reconstruction, we advocate orienting the glandular specimen and also placing surgical clips at the tumor margins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, reconstructive techniques that involve relocation of glandular tissue make reexcision difficult in cases where close or positive margins are observed in the permanent abnormality. 4 Although the lateral thoracodorsal fasciocutaneous flap technique did not obscure the original lumpectomy space, careful and coordinated planning with the oncologic surgeon is important in the event that reexploration is necessary. Similar to reduction mammaplasty reconstruction, we advocate orienting the glandular specimen and also placing surgical clips at the tumor margins.…”
Section: Discussionmentioning
confidence: 99%
“…Because the flap is not an axial flap, flap vascularization to the most distant parts is difficult to predict. 4,13 This situation can predispose to partial necrosis (skin and fat) and an undesirable result. Although our study demonstrated a low incidence of flap complications, care must be taken in high-risk patients such as smokers and patients with associated comorbid diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Вероятность получения не-гативного, с косметической точки зрения, результата после выполненной органосохраняющей операции, до внедрения в онкологию понятия качество жизни, была столь же часто встречаема, как и выполнение мастэктомии. Поэтому по-иски наиболее оптимального решения, которое сочетало бы онкологические принципы и понимание целостности органа, привели к развитию онкопластической хирургии, позволяющей без пренебрежения основными принципа-ми онкологии выполнить не только щадящее лечение, но и сохранить орган (молочную железу) в том виде, который ненамного отличал бы железу от исходного варианта [11,12]. Существует два основополагающих принципа, важных для получения хорошего результата: 1) выбор правильной методики операции на молочной железе; 2) коррекция контралатеральной молочной железы.…”
Section: Discussionunclassified
“…Железы размером А-С; 4. Желание пациентки сохранить молочную железу [4,10]. В ряде слу-чаев (у 5 больных) понадобилась редукционная пластика контрлатеральной молочной железы с целью достижения максимальной симметрии.…”
Section: материалы и методыunclassified